Evaluation of INSAT-3D derived TPW with AIRS retrievals and GNSS observations over the Indian region. Issue 3 (1st February 2020) - Rao, V.K.; Mitra, A.K.; Singh, K.K.; Bharathi, G.; Kumar, Ravi Ranjan; Ray, Kamaljit; Ramakrishna, Ssvs
ABSTRACT: Precipitable water vapor is an important and highly atmospheric variable in temporal and spatially; the knowledge of its variability is important for meteorological and climatological studies. The main objective of this paper, an evaluation of Total Precipitable Water (TPW) retrieved from the Indian National Satellite System (INSAT-3D) data provided by the INSAT-3D Meteorological Data Processing System (IMDPS) at National Satellite Meteorological Centre (NSMC), New Delhi along with collocated Atmospheric Infrared Sounder (AIRS) L3 Standard Physical Retrievals (AIRS-only) during a one year period 2017 over the Indian region. The spatiotemporal distribution of seasonal mean and monthly dependency of the correlation coefficient, bias and root mean square error (RMSE) was computed between INSAT-3D TPW and AIRS retrievals during both daytime and nighttime. The results of the intercomparison reveal that TPW from the INSAT-3D is in very good agreement with the AIRS, that is seasonally distribution of TPW larger in warm seasons (June, July, August) and smaller in the cold season (December, January, February) and monthly dependency of correlation coefficient (> 0.8), bias (2–3 mm) and RMSE (< 5 mm) in all months during both daytime and nighttime, except June, July, August over coastal regions of Arabian Sea and Bay of Bengal shows degradation performance. However, the statistical analysis between INSAT-3D with respect to AIRS TPW retrieval during both daytime and nighttime shows that more reliable except during cloudy days. In addition to it, a similar analysis is carried out to assess the relative performance of INSAT-3D retrieved TPW with respect to 10 Global Navigational Satellite System (GNSS) over the Indian subcontinent obtained from the NSMC the period from 1 st January to 30 June 2017 on hourly. In this analysis, for each station time series, diurnal variations of TPW and monthly, seasonal distribution of the Taylor diagram was carried out between INSAT-3D and GNSS retrievals. INSAT-3D and 10 GNSS stations gave comparable accuracies during the months of March to June whereas the quality degrades in January and February months resulting in slight error. It might be caused by the in the winter season the surface emissivity could be one region for more degraded performance under the drier condition it brings in more uncertainties in surface emissivity. Overall, these results give good confidence in the quality and potential of INSAT-3D over the Indian region and can be used in weather forecasting and nowcasting applications.